À propos des modes de construction du territoire en pays jóola : sources écrites, traditions villageoises et matériaux ethnographiques - Odile Journet-Diallo (Afriques)
In the accounts about the “Felupos” (now called Dyola) left by successive travelers who visited the coastal area of the “southern rivers” between the 15th and the 18th century, two key points stand out: the level of techniques used in rice-farming (evidence of settlement in the distant past) and the hostility toward, and refusal of, trade with white people. Texts from the 18th century provide a glimpse of the complexity of territorial divisions, which becomes even clearer in the writings left by 19th-century colonial officials. Unable to rely on any institution organized as a chieftaincy or clan in these societies, which resisted centralized authority, the setting of administrative boundaries encountered another difficulty, namely the instability of territorial units and of the latter’s relations with each other. In a context where geographical and language boundaries did not coincide, the interplay between the names used by groups and the names that other groups gave to them further complicated matters. What information is available to help us not only explain the names for territorial units (and their bounds) but also understand how the Dyola “constructed” their territorial organization? We can try to draw information from: village oral traditions, the topography of shrines, attendance at ceremonies and, too, the marks left on the landscape itself.